2018
DOI: 10.1111/jocn.13993
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of asthma education materials for school‐age children: Implications for health literacy

Abstract: The present results may help healthcare providers to understand children's capacities to manage their disease, effectively address children's requirements and function as a key resource for children to strengthen their literacy in asthma management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Furthermore, health literacy data can help health professionals to evaluate health education needs, as an effective evaluation tool to guild appropriate disease-specific intervention. There are a number of related studies on health literacy measurements for specific diseases such as type 2 diabetes [3335], hypertension [3638], asthma [39, 40], and AIDS [4143]. However, similar study on TB is not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, health literacy data can help health professionals to evaluate health education needs, as an effective evaluation tool to guild appropriate disease-specific intervention. There are a number of related studies on health literacy measurements for specific diseases such as type 2 diabetes [3335], hypertension [3638], asthma [39, 40], and AIDS [4143]. However, similar study on TB is not yet available.…”
Section: Introductionmentioning
confidence: 99%
“… 23 This multitool assessment method has been applied to PEMs for chronic kidney disease, heart failure and asthma. 24–26 The evaluation results of text factors suggest that the average reading level of materials is often higher than the educational level of readers. For non-text factors, PEMs perform well in terms of layout but not well in pictures, cultural appropriateness and content.…”
Section: Introductionmentioning
confidence: 99%
“…The health literacy of children has been specifically investigated in a number of other areas. Tzeng and Gau (2018) collected 25 pieces of asthma education material for children and interviewed five children (age 8–12 years) about the materials and their usefulness in assisting the children to manage their asthma. Tzeng and Gau (2018) found that most of the education materials were written above the reading ability of school-age children, with only one brochure having a reading level suitable for children in fifth grade or below.…”
Section: Introductionmentioning
confidence: 99%